Incorporating Farmers’ Market Tours into the Expanded Food and Nutrition Education Program: Best Practices and Lessons Learned - Annie Hardison-Moody; J. Dara Bloom; Lorelei Jones; Tony Benavente (Journal of Human Sciences and Extension, 2018)
Research indicates that low-income consumers are less likely to shop at farmers’ markets and that these individuals are often those with the lowest intake of fresh fruits and vegetables. This project aimed to improve familiarity with farmers’ markets among low-income consumers through guided tours of farmers’ markets, implemented as part of the Expanded Food and Nutrition Education Program (EFNEP). EFNEP Program Assistants (PAs) in five counties in North Carolina received training and partnered with a local Cooperative Extension agent to deliver a farmers’ market tour at the mid-point of a nine-lesson series on healthy eating. Forty-eight participants completed the series, completing a pre-and post-class series behavior change assessment and dietary recall. At entry, 54% of participants said they ate food that came from a local farm, compared to 94% at exit. Interviews with all PAs found that participants: plan to visit the farmers’ market again in the future, tried new recipes with foods purchased at the market, and learned how to talk with and ask questions of farmers’ market vendors. We argue that farmers’ market tours are a promising strategy for increasing familiarity with local foods, when carried out as part of a series of nutrition education classes.